PERFORMATIVITAS GENDER DALAM FILM FUNERAL PARADE OF ROSES - Muhammad Berlian Nuansa Adidaya (2020)
This study analyzes the film Funeral Parade of Roses through the perspective of gender performativity theories introduced by Judith Butler. Performativity processed from various scenes throughout the film that contain ideas about transgenderism. These ideas developed in the Shinjuku ecosystem which at the time became an epicentrum for counter-culture activities in Tokyo. Gay bar scenes is growing as a new industry in the community. The film follows the story of Eddie who works at a bar called Genet. Based on these ideas, the research question is, how is gender performance displayed in the film Funeral Parade of Roses? This study uses qualitative methods with discourse analysis techniques developed by Teun A. Van Dijk with three structures in understanding language, namely macro structure (thematic), superstructure (schematic), and micro structure (semantic, syntactic, stylistic, and rhetorical). Finding shows that Funeral Parade of Roses displays gender performativity through a variety of scenes that show transgender women perform performative actions that are identical to women. Gender is described as an imitative stucture so that transgender women in this film can construct their own femininity through various ways. Keywords: gender, transgenderism, gender performativity, film